Pembelajaran Bahasa Arab di Mahad Sunan Ampel Al-Aly melalui pendekatan sosiolinguistik - Asshiddiqi, Akhmad Irsyad; Mukarromah, Inayatul (Aksara: Jurnal Bahasa dan Sastra, 2023)
The purpose of writing this article is to describe the process of forming the language environment in Mahad Sunan Ampel Al-Aly from a sociolinguistic perspective and describe the inhibiting factors for the formation of a linguistic environment in Mahad Sunan Ampel Al-Aly from the perspective of behavioral learning theory. In this writing, the writer uses a qualitative approach with descriptive writing types. There are three data collection tools used, namely: interviews, observation, and documentation. The results of writing are as follows: 1) The process of forming a language environment in Mahad Sunan Ampel Al-Aly in terms of sociolinguistics consists of memorizing vocabulary and assembling it into sentences, and getting used to using language in everyday life. 2) The inhibiting factors for the formation of the linguistic environment in Mahad Sunan Ampel Al-Aly in terms of sociolinguistics are environmental conditions that are still not supportive, many student activities are carried out outside the mahad. The author's suggestion for Mahad Sunan Ampel Al-Aly is that in order for the formation of the language environment to be more optimal, it is necessary to hold penalties for students who do not follow the rules that have been set. because basically language learning based on speaking skills depends on the habits of students to speak, a teacher must force his students to speak the language being studied. because by being forced, students will get used to it.Keywords: language learning, sociolinguistics, language environment